2023
DOI: 10.1155/2023/6613670
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical Profiles and Anticancer Effects of Calophyllum inophyllum L. Extract Relating to Reactive Oxygen Species Modulation on Patient-Derived Cells from Breast and Lung Cancers

Abstract: Reactive oxygen species (ROS) contribute to cancer growth and metastasis. Using antioxidants to modulate cellular ROS levels is a promisingstrategy for cancer prevention and treatment. Calophyllum inophyllum L., or tamanu, is a medicinal plant renowned for its anti-inflammatory, antioxidant, and anticancer properties in traditional medicine systems. However, the anticancer effects of C. inophyllum extract on cellular ROS remain unexplored. This study represents the first report on such effects and provides the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…According to Léguillier et al [6], bioactive fatty acids from the seed oil exhibited accelerated in vitro wound closure, the healing factor being 1.3 to 2.1 higher compared to control, and distinct antibacterial activity against Staphylococcus aureus strain involved in skin infections. The authors also reported the lowest and highest cytotoxicity value at LC 50 18.7% and 7.3%, respectively. The bioactive compound (4-(3-methylazetidin-1-yl) pentan-2-ol) of C. inophyllum seeds oil demonstrated potent antibacterial activities (17 ± 1.73 to 24 ± 1.15 mm) against Bacillus subtilis, Staphylococcus aureus, Escherichia coli, Klebsiella pneumoniae, and Pseudomonas aeruginosa [12].…”
Section: Major Bioactive Compounds Of C Inophyllum and Their Therapeu...mentioning
confidence: 90%
See 3 more Smart Citations
“…According to Léguillier et al [6], bioactive fatty acids from the seed oil exhibited accelerated in vitro wound closure, the healing factor being 1.3 to 2.1 higher compared to control, and distinct antibacterial activity against Staphylococcus aureus strain involved in skin infections. The authors also reported the lowest and highest cytotoxicity value at LC 50 18.7% and 7.3%, respectively. The bioactive compound (4-(3-methylazetidin-1-yl) pentan-2-ol) of C. inophyllum seeds oil demonstrated potent antibacterial activities (17 ± 1.73 to 24 ± 1.15 mm) against Bacillus subtilis, Staphylococcus aureus, Escherichia coli, Klebsiella pneumoniae, and Pseudomonas aeruginosa [12].…”
Section: Major Bioactive Compounds Of C Inophyllum and Their Therapeu...mentioning
confidence: 90%
“…Based on their findings, the branches extract contains several bioactive compounds (antiarol, syringol, 5-hydroxymethylfurfural, pyrocatechol, 2,3-dihydro-3,5-dihydroxy-6-methyl-4Hpyran-4-one, 2-methoxyhydroquinone) which exhibited strong antioxidant activity and no cytotoxicity in the first 24 h of treatment. Nevertheless, it showed notable antiproliferative effects after 72 h [18].…”
Section: Name Of Compound Pharmacological Property Plant Part Used Re...mentioning
confidence: 98%
See 2 more Smart Citations